The advantages of intensively teaching english in public schools from seventh grade to the second year of high school in El Salvador - Núñez Barrera, Haydee Beatriz
The FLD began to work in order to create new majors with Teachers from the United States of America, France and El Salvador. Throughout the world, the teaching of foreign languages has increased. The teaching and learning of English was not for the purpose of reading and translating documents any more; the new purpose was for communications. “At UES a new method started to be used in 1986, this was The Communicative Method. At that time they started to use communicative grammar books, they worked hard to teach English, through speaking, the language was associated to thoughts and not only to the phonology.” R. Labrador (Personal communication. May 26th, 2006). The different nations were closer every time, and they saw the necessity of counting on people who could communicate with speakers of other languages. In the classroom, teachers were looking for more effective ways for students to learn English in a faster and precise manner. The Language Department at UES continued working in the creation of the definitive plans for the “Profesorado” and Bachelor degrees in English. These plans became effective on August 14, 1973. The objectives of these plans were, to prepare new professionals in different areas, such as bank, industry, commerce, Linguistics and Literature research, and teaching. Such plans offered an abundant work field to the new professionals, due to its objectives, which covered a wide portion of the national labor.